Effects of Level of Immersion on Virtual Training Transfer of Bimanual Assembly Tasks - Shen, Songjia; Chen, Hsiang-Ting; Raffe, William; Leong, Tuck Wah (Frontiers in Virtual Reality, 2021)
The availability of consumer-facing virtual reality (VR) headsets makes virtual training an attractive alternative to expensive traditional training. Recent works showed that virtually trained workers perform bimanual assembly tasks equally well as ones trained with traditional methods. This paper presents a study that investigated how levels of immersion affect learning transfer between virtual and physical bimanual gearbox assembly tasks. The study used a with-in subject design and examined three different virtual training systems, i.e., VR training with direct 3D inputs (HTC VIVE Pro), VR training without 3D inputs (Google Cardboard), and passive video-based training. 23 participants were recruited. The training effectiveness was measured by participant’s performance of assembling 3D-printed copies of the gearboxes in two different timings: immediately after and two weeks after the training. The result showed that participants preferred immersive VR training. Surprisingly, despite being less favourable, the subjects’ performance of video-based training were similar to training on HTC VIVE Pro. However, video training led to a significant performance decrease in the retention test session two weeks after the training.